2018
DOI: 10.9734/ijbcrr/2018/41986
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Changes in Host Defense Enzymes in Response to Fusarium Wilt in Pigeonpea (Cajanus cajan (L.) Millspaugh)

Abstract: This work was carried out in collaboration between both authors. Author JD collected and maintained the pathogen and host cultivars, performed pot experiment for disease development, performed enzyme analyses of collected host tissue samples and recorded the data. Author NL proposed conception of the study concerning defense enzyme analysis, prepared experimental plan, discussed the results and prepared the manuscript. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Similarly, Maheshwari et al (2019) reported that seed treatment with B. subtilis strain (CPHR3) was the most effective in promoting chickpea growth in pots under screen house conditions. Datta and Lal (2012) also correlated Fusarium wilt resistance with phenol content in chickpea varieties and observed maximum phenol content (21.8 mg gdw −1 ) in wilt-resistant cultivars and minimum (16.5 mg gdw −1 ) in susceptible lines of chickpea.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Maheshwari et al (2019) reported that seed treatment with B. subtilis strain (CPHR3) was the most effective in promoting chickpea growth in pots under screen house conditions. Datta and Lal (2012) also correlated Fusarium wilt resistance with phenol content in chickpea varieties and observed maximum phenol content (21.8 mg gdw −1 ) in wilt-resistant cultivars and minimum (16.5 mg gdw −1 ) in susceptible lines of chickpea.…”
Section: Discussionmentioning
confidence: 86%
“…These chemical ingredients exhibit varied endogenous functions, specifically primary metabolites are directly involved in the growth and development of plants whereas secondary metabolites are known to protect plants from various abiotic and biotic stresses 4 . Various groups of secondary metabolites including phenolic compounds, flavanoids, steroids, triterpenoids, alkaloids, isoflavanoquinones, anthocyanins, toxalbumin are known 5,6 .…”
Section: Introductionmentioning
confidence: 99%